Rebamipide does not protect against naproxen-induced gastric damage: a randomized double-blind controlled trial. Issue 1 (December 2016) - Gagliano-Jucá, Thiago; Moreno, Ronilson; Zaminelli, Tiago; Napolitano, Mauro; Magalhães, Antônio; Carvalhaes, Aloísio; Trevisan, Miriam; Wallace, John; De Nucci, Gilberto
Abstract Background Rebamipide is a gastroprotective agent with promising results against gastric damage induced by non-steroidal anti-inflammatory drugs. The present study evaluated if rebamipide protects against naproxen-induced gastric damage in healthy volunteers. Changes in gastric PGE2 tissue concentration were also evaluated. Methods After a preliminary endoscopy to rule out previous gastric macroscopic damage, twenty-four healthy volunteers of both sexes were divided into 2 groups. One group received sodium naproxen 550 mg b.i.d. plus placebo for 7 days, while the other group received sodium naproxen 550 mg b.i.d. plus rebamipide 100 mg b.i.d. At the end of treatment, a new endoscopy was performed. Gastric macroscopic damage was evaluated by the Cryer score and by the modified Lanza score. The primary outcome measure of the trial was the macroscopic damage observed in each treatment group at the end of treatment. Biopsies were collected at both endoscopies for PGE2 quantification and histopathological analysis (secondary outcomes). Tissue PGE2 was quantified by ELISA. The randomization sequence was generated using 3 blocks of 8 subjects each. Volunteers and endoscopists were blind to whether they were receiving rebamipide or placebo. Results All recruited volunteers completed the trial. Sodium naproxen induced gastric damage in both groups. At the end of the study, median Cryer score was 4 in both groups (Difference = 0; 95%CI = −1 to 0;p  = 0.728). In the placebo group, the mean tissue PGE2 concentration was 1005 ± 129 pg/mL before treatment and 241 ± 41 pg/mL after treatment (p  < 0.001). In the rebamipide group, the mean tissue PGE2 concentration was 999 ± 109 pg/mL before treatment, and 168 ± 13 pg/mL after treatment (p  < 0.001). There was no difference in mean tissue PGE2 between the two groups (difference = 5; 95%CI from −334.870 to 345.650;p  = 0.975). No significant change was observed at the histopathological evaluation, despite the evident macroscopic damage induced by naproxen. Conclusion Rebamipide does not protect against naproxen-induced gastric damage in healthy volunteers. Trial registration ClinicalTrials.gov, NCT02632812 . Registered 14 December 2015.